Effects of Covid-19 on the happiness index among construction related student in UiTM Cawangan Sarawak / Syarifah Nazira Mohd Osman - Mohd Osman, Syarifah Nazira (2021)
Higher Education benefits the nation as it drives innovation and aimed to find solutions to global challenges in areas that matter to society such as healthcare, environmental protection, resource security, international development and population trends. However, the COVID-19 pandemic has negatively affected many individuals and the entire educational system where many countries have decided to close schools, colleges, and universities. This measure was intended to contain the spread of the virus and as a result, the traditional teaching and learning in physical classroom has shifted to Online Distance Learning (ODL) either synchronously or asynchronously by UiTM Cawangan Sarawak’s academicians and students on an unprecedented scale. Therefore, this research aims to assess the effects of COVID-19 on the happiness index among construction related student in UiTM Cawangan Sarawak in view of ODL. 288 number of students from Fakulti Senibina, Perancangan dan Ukur (FSPU) UiTM Cawangan Sarawak have volunteered to participate to online questionnaires and interviews that were conducted for the purpose of this study. The questionnaires and interview questions were constructed of demographic questions, Lifestyle Questionnaire (LSQ) and Oxford Happiness Questions (OHQ); to assess the lifestyle, happiness index and making comparison of the lifestyle and happiness index of the respondents before and in the time of COVID-19 pandemic. The result of this research shows that construction related students are mentally drained and most of their lifestyle and habits are influenced by their emotion and readiness. Numerous aspects in students’ lifestyle are also changes due to COVID-19 pandemic. Thus, this research opts to create awareness among construction related students on how to manage their happiness index and lifestyle. Youth mental health prevention and early intervention programmes can be implemented since personal and environmental coping resources are important for students’ wellbeing.